PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS V UPT SDI BONTOALA I KABUPATEN GOWA (STUDI EKSPERIMEN SEMU) (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the Problem Based Learning (PBL) model on the reading comprehension skills of fifth-grade students at UPT SDI Bontoala I. This study employs a quantitative approach using a quasi-experimental design in the form of a non-equivalent control group design. The study population consists of all fifth-grade students at UPT SDI Bontoala I for the 2024/2025 academic year, with a sample size of 61 students comprising 32 students in the experimental class and 29 students in the control class. Data collection techniques included reading comprehension tests (pretest and posttest), observation, and documentation. Data were analyzed using descriptive and inferential statistics with the aid of SPSS version 24, including normality tests, homogeneity tests, and independent samples t-tests. The results of the study indicate that the experimental class’s posttest mean score of 77.19 showed an increase of 17.03 points from the pretest score of 60.16. Meanwhile, the control class achieved a posttest mean score of 62.59 with an increase of 8.45 points from the pretest score of 54.14. The results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, thereby accepting the alternative hypothesis. Thus, it can be concluded that the implementation of the Problem-Based Learning model significantly influenced the improvement in reading comprehension skills of fifth-grade students at UPT SDI Bontoala I.